Quality Control Analysis of Reject Products in the Multiline Machine Packaging Process Using the Statistical Quality Control (SQC) Method - Olivia Safa Salsabila Ali; Budi Hariono (The University of Lampung, 2025)
Food packaging is used to wrap products in order to protect them from external contamination, including ensuring food safety. Multiline machine is commonly used as the form of packaging. The problem is, the product that is rejected is often surpass the standard limits that has been set by the company. This study aims to identify the types of rejects that often occur, identify rejects that are still within the control limits or not and what factors cause reject products. Statistical Quality Control (SQC) method with seven control tools is used within this research. The study concludes there were 6 types of rejects produced by the multiline machine. 3 of the highest rejects types on the pareto diagram of the multiline machine, namely leaking as many as 5,550 sachets for percentage of 28.16%, reject cutter as many as 4,760 sachets for percentage of 24.21% and packaging precision as many as 4,180 sachets for percentage of 21.21% with a cumulative percentage of 73.52%. After being revised, the results of the reject control chart analysis are still within the control limits, but still with high amounts of rejects. Materials, machines, people, and methods are the factors that affect products to be rejected. Keywords: Control chart, Multiline machines, Packaging, Reject Statistical Quality Control (SQC)